Denial of service in wireless sensor networks: issues and challenges - Pathan, Al-Sakib Khan (Nova Science Publishers, Inc., 2010)
Wireless Sensor Network (WSN), composed of a huge number of resource-constrained sensors can be used for a large number of securitysensitive applications. Regardless of the type of application, smooth collection and delivery of data from this type of network is one of the critical requirements. If the data supply process is hampered and thus the expected services become unavailable due to the intentional attempts of the adversaries, we consider this as a Denial of Service (DoS) attack. As DoS attack targets to jeopardize the usual services, it can often drastically curtail the utility of wireless sensor network. In this short communication, we explore the meaning of DoS in WSN, its effective mitigation techniques, and recent issues and challenges in this research area.